2013
DOI: 10.1590/s0102-09352013000600005
|View full text |Cite
|
Sign up to set email alerts
|

Maturação in vitro de oócitos bovinos em meios suplementados com quercetina e seu efeito sobre o desenvolvimento embrionário

Abstract: RESUMOA quercetina é um flavonoide, amplamente encontrada em frutas, vegetais, grãos, flores, com elevada concentração no vinho tinto, e tem sido caracterizada funcionalmente pela atividade antioxidante. Para avaliação da maturação nuclear e do desenvolvimento embrionário bovino, os oócitos foram maturados por 22h na presença de quercetina (0,4, 2, 10 e 50M), cisteamina (100M) e na ausência dos antioxidantes. Os oócitos maturados foram corados com Hoechst para avaliação da maturação in vitro. Para avaliação … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
4
0
4
Order By: Relevance
“…Thus, it is plausible to see an increasing number of reports emphasizing the beneficial role of the antioxidant supplementation of maturation medium to overcome oxidative stress [ 35 ]. Multiple studies reported an increase in blastocyst rate when the IVM medium was supplemented with different antioxidants, such as nobiletin [ 36 ], quercetin [ 37 ], vitamin C [ 38 ], and resveratrol [ 39 ]. Chowdhury et al [ 10 ] were the first to evaluate the effect of lycopene in IVM in a bovine model.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is plausible to see an increasing number of reports emphasizing the beneficial role of the antioxidant supplementation of maturation medium to overcome oxidative stress [ 35 ]. Multiple studies reported an increase in blastocyst rate when the IVM medium was supplemented with different antioxidants, such as nobiletin [ 36 ], quercetin [ 37 ], vitamin C [ 38 ], and resveratrol [ 39 ]. Chowdhury et al [ 10 ] were the first to evaluate the effect of lycopene in IVM in a bovine model.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) are common metabolites produced during IVM of oocytes. Physiological levels of ROS are necessary for normal development of oocytes, and ROS act as signaling molecules and regulate the cell development cycle and apoptosis ( Guemra et al, 2013 ). However, high levels of ROS can be generated during IVM because of excessive in vitro manipulation of oocytes and hyperoxia stress, which is a negative factor affecting the IVM rate of oocytes ( Pu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The IVP process for cattle involves several steps, from the oocyte collection in the farms to the laboratory. Moreover, factors inherent or not inherent to the donor, such as race, age, estrous phase, nutrition, seasonality , hormone stimulation (Silva et al, 2017), number of OPU sessions (Gimenes et al, 2015), embryo culture media (Guemra et al, 2013), and semen used for in vitro fertilization (IVF) (Fernandéz-Gonzalez et al, 2008) can affect the results.…”
Section: Introductionmentioning
confidence: 99%